“Spyt kom te laat” The development and evaluation of a health-related fotonovela about methamphetamine (“tik”) use in the Western Cape and Northern Cape provinces of South Africa - Davis, Herbert Douglas (Stellenbosch : Stellenbosch University, 2017)
Thesis (PhD Document analysis and design)--Stellenbosch University, 2017.